COMPLIANCE OF THE RESISTANCE CAPACITY OF ELITE ATHLETES FROM DIFFERENT TYPES OF COMBAT SPORTS WITH THE COMPETITIVE DEMANDS OF MIXED MARTIAL ARTS - Savenko, A.; Chernozub, A.; Aloshyna, A. (Rehabilitation and Recreation, 2025)
Purpose. To determine the matching of resistance capacity of elite athletes practicing judo, Muay Thai,Greco-Roman wrestling, and boxing, to the loads that are similar in intensity and duration to those encoun-tered in competitive Mixed Martial Arts (ММА).Material and Methods. 90 elite male athletes were examined (33 candidates for the Master of Sport and57 Masters of Sport), aged 15–16 years. Five groups of athletes were formed: judokas, Muay Thai fighters,boxers, MMA athletes, and Greco-Roman wrestlers. Two test loads were proposed. During Test Load 1, participants performed alternating exercises for 3 minutes, a hanging leg raise on a horizontal bar with legsheld straight at a 90° angle, followed by push-ups with full arm flexion and extension. During Test Load 2, each group performed the most powerful and technically demanding combination of movements specificto their respective combat sport for 20 seconds. Heart rate variability (HRV) spectral analysis indices were used to evaluate the athletes’ resistance to the test loads. Assessment included both the basal HRV parameters (VLF, LF, HF, LF/HF) and the changes these parameters exhibited following the test loads.Results. Test Load 1 led to a shift in autonomic balance toward parasympathetic regulation, accompanied by an increase in central regulatory activity, in the examined groups of boxers, Greco-Roman wrestlers, and MMAfighters. In the Muay Thai group, a similar training load resulted in enhanced vagal influence on the sinoatrialnode alongside diminished central regulation of sinus rhythm. In comparison with baseline HRV, the Muay Thai and MMA athletes demonstrated reduced central regulation before Test Load 1 and one hour after recovery.Following Test Load 2, Muay Thai boxers and Greco-Roman wrestlers exhibited a shift in autonomic balancetoward parasympathetic regulation, along with an increase in central regulatory activity. The boxer and MMAgroups showed increased vagal influence on the sinoatrial node in response to Test Load 2, which reflected the technical elements of their respective combat sports, reflecting heightened parasympathetic activity.Conclusions. The results indicate that in 75% of elite athletes from various combat sports, the level ofphysiological resistance is insufficient to effectively implement short-term adaptation mechanisms duringcompetitive MMA loads. A shift of autonomic balance toward parasympathetic activity, even when accopanied by reduced cardiac regulatory tension, does not necessarily indicate effective short-term adaptation.Additional monitoring of changes in the central regulation of sinus rhythm provides insight into whetherthe stressor intensity aligns with the individual’s functional capacity, allowing for timely interventions toprevent possible adaptive failure.